PENGARUH APLIKASI ASAP CAIR TEMPURUNG KELAPA TERHADAP TOTAL MIKROBA DAN KUALITAS ORGANOLEPTIK SE’I DOMBA EKOR GEMUK - Helsy Juniarto Bule Logo; Herianus J. D. Lalel; Dodi Dharmakusuma (Politeknik Pertanian Negeri Kupang, 2021)
This study aims to determine the effect of the application of coconut shell liquid smoke on the total microbes and organoleptic properties of fat-tailed sheep. The design used in this study was a completely randomized design with 4 treatments and 4 replications. The results showed that the R0 treatment had the highest average total value of bacterial colonies compared to others. Meanwhile, for organoleptic quality treatments R0 and R1 had the highest average values for Color, Aroma, and Taste. This study concluded that the application of coconut shell liquid smoke at concentrations of 10%, 20% and 30% significantly reduced the total bacterial colonies compared to the traditional se'i. The application of coconut shell liquid smoke at concentrations of 20% and 30% significantly reduced the panelists' preference for color, aroma and taste, while the concentration of 10% liquid smoke was not significantly different from that of traditional fat-tail sheep se'i. Keyword : Liquid smoke coconut shell, Fat-tailed sheep, Se’i.